Implementation of The Kurikulum Merdeka in Primary Schools - Atsmarani, Fadhilah; Tukiran; Andriani, Ana; Wakhudin (Proceedings Series on Social Sciences & Humanities, 2024)
Many changes to the curriculum in Indonesia have also been made because they follow current developments or could also be due to other things such as changes in leaders including the minister of education, evaluation of the previous curriculum which was deemed less effective, and so on. Various problems that arise during curriculum development need to be reviewed further in depth and analyzed carefully. PeThis study uses a literature review research method. Literature review research is the result of analyzing various information and conceptual data, qualitative data and quantitative data from several research articles published earlier and containing theories related to the implementation of the Kurikulum Merdeka in elementary schools. Results With this curriculum, it is hoped that it can produce advanced teaching in Indonesia, can deepen the potential of students, so this curriculum is deliberately made simple and flexible. In the process of implementing this curriculum, teachers are often faced with various challenges and obstacles. Of course, all elements of education have an important role in improving things that can hinder the implementation of the Kurikulum Merdeka. Therefore, in further studies, a more appropriate arrangement or strategy is needed so that it can be used as an alternative or solution to the obstacles experienced by teachers in the process of implementing the Kurikulum Merdeka in elementary school.